2020
DOI: 10.1371/journal.pone.0237810
|View full text |Cite
|
Sign up to set email alerts
|

Human cardiac fibroblasts expressing VCAM1 improve heart function in postinfarct heart failure rat models by stimulating lymphangiogenesis

Abstract: Cardiovascular diseases are a leading cause of death worldwide. After an ischemic injury, the myocardium undergoes severe necrosis and apoptosis, leading to a dramatic degradation of function. Numerous studies have reported that cardiac fibroblasts (CFs) play a critical role in heart function even after injury. However, CFs present heterogeneous characteristics according to their development stage (i.e., fetal or adult), and the molecular mechanisms by which they maintain heart function are not fully understoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 82 publications
0
24
0
Order By: Relevance
“… 20 Iwamiya et al reported that local injection of human VCAM1-expressing cardiac fibroblasts in a postinfarct rat model led to a significant restoration of LV contraction by mobilizing lymphatic endothelial cells into the infarct area. 21 These angiogenic and lymphangiogenic effects may also contribute to the beneficial effects of HAE seen in the present study. However, the possibility remains that the increases in Icam1 and Vcam1 may simply reflect increases in endothelial cells through the HIF1α-CXCL12/VEGF signaling pathway.…”
Section: Discussionmentioning
confidence: 56%
“… 20 Iwamiya et al reported that local injection of human VCAM1-expressing cardiac fibroblasts in a postinfarct rat model led to a significant restoration of LV contraction by mobilizing lymphatic endothelial cells into the infarct area. 21 These angiogenic and lymphangiogenic effects may also contribute to the beneficial effects of HAE seen in the present study. However, the possibility remains that the increases in Icam1 and Vcam1 may simply reflect increases in endothelial cells through the HIF1α-CXCL12/VEGF signaling pathway.…”
Section: Discussionmentioning
confidence: 56%
“…This population expresses several pro-lymphangiogenic factors, including VEGF-C, and was shown to promote lymphangiogenesis as assessed by assays for in vitro tube formation. Furthermore, injection of human foetal CFV in post-infarct heart failure rat models mobilised LECs into the infarcted area and restored cardiac contractility [158].…”
Section: Lymphangiogenic Therapy Post-mimentioning
confidence: 96%
“…Overexpressed AM induces cardiac lymphangiogenesis after MI, resulting in improved cardiac function and reduced myocardial edema via regulation of connexin 43 [71]. In post-infarct heart failure rat models, cardiac fibroblasts expressing vascular cell adhesion molecule-1 (VCAM-1) improve heart function by triggering lymphangiogenesis [14]. A combined delivery of lymphatic endothelial progenitor cells (LEPCs) and VEGF-C with the functionalized self-assembling peptide (SAP), or delivery of SAP-thymosin β4 (Tβ4) has shown to be effective for enhancing cardiac lymphangiogenesis after MI, reducing cardiac inflammation and edema, attenuating reverse myocardial remodeling, and improving cardiac function and repair of the infarcted myocardium [132,133].…”
Section: Prospective Therapeutic Strategies Targeting Lymphangiogenesis In Cardiovascular Diseasesmentioning
confidence: 99%
“…The important findings suggest that the use of REELIN could be a valuable therapeutic approach to improve cardiac function in humans [12]. Moreover, a growing body of evidence indicates that lymphangiogenesis is an active participant in the pathogenesis of atherosclerosis and myocardial infarction (MI) [13][14][15]. Vascular endothelial growth factor C (VEGF-C) and its receptor VEGFR-3 facilitate lymphangiogenesis and lymphatic function, which may provide a pathway for inflammatory cell efflux, favoring the resolution of cardiac edema and wound healing within the injured heart [16].…”
Section: Introductionmentioning
confidence: 99%